Tinjauan Hukum Islam Terhadap Iddah dan Ihdad Wanita Karier : (Studi Kasus Di Kecamatan Sumber Ketempa Kecamatan Kalisat Kabupaten Jember ) - Alfina Wildatul Fitriyah (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2019)
The concept of Iddah and Ihdad for career women in the Quran, alHadith and KHI Law responds that career women are women who play a dual role, namely as a mother and as the backbone of the family, the existence of career women here helps the economic survival of the family. The discussion in this study aims to reveal everything related to women's freedom to carry out activities outside the home, but there are also demanding and restrictive religious prescriptions that must be informed by research. The research method used is qualitative field research with a qualitative descriptive approach. Data collection techniques are carried out by observation, interviews and documentation. To get these answers, researchers used primary and secondary data. Both data were analyzed using qualitative analysis methods. Based on research in Sumberketempa Hamlet, Kalisat District, it was found that many women whose husbands died or divorced do not know the time of Iddahh according to Islamic teachings. They only follow the local village customs. From the above results it can be concluded that a permanent working woman is required to complete the Iddahh and Ihdad periods and is not allowed to accept proposals from other men or marry other men during the Iddahh period. However, in the case of Ihdad it is permissible if the matter is urgent and cannot be represented